2018
DOI: 10.1016/j.tust.2018.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the thermal performance of building envelopes for energy saving in underground office buildings in various climates of China

Abstract: This article investigates the influence of the thermal performance of building envelopes on annual energy consumption in a ground-buried office building by means of the dynamic building energy simulation, aiming at offering reasonable guidelines for the energy efficient design of envelopes for underground office buildings in China. In this study, the accuracy of dealing with the thermal process for underground buildings by using the Designer's Energy Simulation Tool (DeST) is validated by measured data. The an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 25 publications
(34 reference statements)
0
20
0
Order By: Relevance
“…This indicates three phases as shown in Figure 14. In [123], optimizing the thermal performance of building envelopes for energy consumption saving was performed in office buildings in China for various climates. In [124], multi-objective optimization and the analysis of parametric of a solar heating system were investigated for different building envelopes.…”
Section: Sustainability 2020 12 X For Peer Review 18 Of 38mentioning
confidence: 99%
“…This indicates three phases as shown in Figure 14. In [123], optimizing the thermal performance of building envelopes for energy consumption saving was performed in office buildings in China for various climates. In [124], multi-objective optimization and the analysis of parametric of a solar heating system were investigated for different building envelopes.…”
Section: Sustainability 2020 12 X For Peer Review 18 Of 38mentioning
confidence: 99%
“…In view of the examination of selected segments, this investigation demonstrated that there is a critical potential for improving the natural capability of low-ascent buildings, by choosing appropriate parts and materials, continuing the energy execution of the building. The exactness of managing the thermal procedure received for underground buildings by utilizing DeST is approved by estimated information by Shi, L., et al, 2018 [23]. The examined outcomes demonstrated that the yearly energy utilizations for this kind of buildings change altogether, and it depends on the estimation of the general thermal exchange coefficient (U-value) of the envelopes.…”
Section: Thermal Performance Of Building Components Insulating By Polmentioning
confidence: 99%
“…Therefore, the reduction of building energy consumption is crucial in order to achieve the goals in terms of decarbonization recently established in Paris Agreement. To this scope, several actions are required, such as: building envelope refurbishments [140][141][142], optimization of the HVAC systems [143][144][145][146][147][148][149], utilization of renewable energy sources [150][151][152][153][154][155][156]. This topic was initially marginally investigated during the first SDEWES conferences.…”
Section: Building Efficiencymentioning
confidence: 99%